The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10265-011-0434-x
|View full text |Cite
|
Sign up to set email alerts
|

The ABA-mediated switch between submersed and emersed life-styles in aquatic macrophytes

Abstract: Hydrophytes comprise aquatic macrophytes from various taxa that are able to sustain and to complete their lifecycle in a flooded environment. Their ancestors, however, underwent adaptive processes to withstand drought on land and became partially or completely independent of water for sexual reproduction. Interestingly, the step backwards into the high-density aquatic medium happened independently several times in numerous plant taxa. For flowering plants, this submersed life-style is especially difficult as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 97 publications
1
32
0
Order By: Relevance
“…Parallels are seen between this situation and that of leaf complexity, where other mechanisms besides the KNOX-GA gene module have been shown to operate in a derived clade of Fabaceae (Hofer et al, 1997;Champagne et al, 2007;Zhou et al, 2014). Since the acquisition of heterophylly has also occurred independently multiple times (Wells and Pigliucci, 2000;Wanke, 2011;Nakayama et al, 2012a), the core regulatory mechanisms for acquisition of heterophylly may not be conserved during evolution.…”
Section: Regulation Of Ga Level Via Knox1 Genes Induces Heterophyllymentioning
confidence: 99%
See 1 more Smart Citation
“…Parallels are seen between this situation and that of leaf complexity, where other mechanisms besides the KNOX-GA gene module have been shown to operate in a derived clade of Fabaceae (Hofer et al, 1997;Champagne et al, 2007;Zhou et al, 2014). Since the acquisition of heterophylly has also occurred independently multiple times (Wells and Pigliucci, 2000;Wanke, 2011;Nakayama et al, 2012a), the core regulatory mechanisms for acquisition of heterophylly may not be conserved during evolution.…”
Section: Regulation Of Ga Level Via Knox1 Genes Induces Heterophyllymentioning
confidence: 99%
“…Some leaf form alterations are thought to be an adaptive response to the environment (Cook and Johnson, 1968). In addition, heterophylly is seen across diverse plant species (Wells and Pigliucci, 2000;Wanke, 2011;Nakayama et al, 2012a). Hence, heterophylly provides a good model to understand geneenvironment interactions (Pigliucci, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit forms with weak serrate or deep lobed margins in terrestrial environments and become pinnately compound in submerged aquatic environments (Figures 1(D)-(G)) [7,8]. Although heterophylly is widely noted among diverse plant species from ferns to angiosperms [8][9][10], little is known about the mechanism that regulates this phenomenon, because of the lack of an adequate model species. A previous study indicated that lake cress has some advantages as a model for studying heterophylly, such as plant size, easy maintenance, and systematic positioning (closely related to Arabidopsis) [8].…”
Section: Introductionmentioning
confidence: 99%
“…3 Several plants showing heterophylly have been described and the underlying mechanisms have been investigated. 1,4,5 These studies have shown that various hormones, such as ethylene and abscisic acid, are involved in the alteration of leaf form.…”
Section: Heterophylly In Rorippa Aquaticamentioning
confidence: 99%